2020
DOI: 10.7150/jca.40339
|View full text |Cite
|
Sign up to set email alerts
|

miR-488-3p sponged by circ-0000495 and mediated upregulation of TROP2 in head and neck squamous cell carcinoma development

Abstract: TROP2 (trophoblast cell surface antigen 2) overexpression has been reported in many human cancers. The correlation between TROP2 and tumor aggressiveness has implied it could be a prognostic indicator. However, the roles of TROP2 and their underlying mechanisms remain of great interest in head and neck squamous cell carcinoma (HNSCC) biology. In the current study, the prognostic significance of TROP2 in HNSCC archival samples was determined using immunohistochemistry. Quantitative reverse transcriptase PCR (qR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Head and neck squamous cell carcinoma (HNSCC) is the sixth most common type of human malignancy and involves carcinoma of several anatomic sites, such as lip, oral cavity, pharynx (nasopharynx, oropharynx, hypopharynx), and larynx, with an annual incidence of~600,000 per year (12,13). Although the diagnosis and treatment have advanced in recent years, HNSCC still has a high incidence and mortality rate in developing countries (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC) is the sixth most common type of human malignancy and involves carcinoma of several anatomic sites, such as lip, oral cavity, pharynx (nasopharynx, oropharynx, hypopharynx), and larynx, with an annual incidence of~600,000 per year (12,13). Although the diagnosis and treatment have advanced in recent years, HNSCC still has a high incidence and mortality rate in developing countries (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic factors were identified as important modulators of Trop2 expression in cancers, too. Hao et al recently described circRNA—miR-488-3p—Trop2 regulatory loop that released Trop2 epigenetic silencing in head-and-neck squamous cell carcinoma cell lines [ 118 ]. Other miRNAs that target Trop2 were also identified in head-and-neck carcinoma [ 134 ] and urothelial bladder cancer [ 135 ].…”
Section: Trop2 In Cancermentioning
confidence: 99%
“…Wang et al 36 revealed that circRNA_103862 promotes the proliferation and invasion of laryngeal squamous cell carcinoma through targeting the miR‐493‐5p/GOLM1 axis, and it might serve as a prognostic indicator and anti‐cancer target for laryngeal squamous cell carcinoma. Hao et al 37 found that upregulated circ‐0000495 mediates overexpression of TROP2 by sponging miR‐488‐3p to promote tumor progression and is associated with patient survival in HNSCC. Here, we explored the potential biological function of hsa_circ_0016148 in HNSCC tumorigenesis through bioinformatics analysis by constructing a hsa_circ_0016148‐miRNA‐mRNA interaction network.…”
Section: Discussionmentioning
confidence: 99%